Dampak Penerapan Akuntansi Syariah terhadap Nilai Perusahaan dengan Perkembangan Akuntansi Syariah Saat Ini - Satrya Mutthaqin; Raju Adha; Nurlaila Nurlaila (Universitas Muhammadiyah Surabaya, 2023)
ABSTRACTIslamic accounting has become an increasingly important topic in the global business context. The application of sharia accounting in companies can have a significant impact on company value. Many companies have turned to Islamic accounting to meet market demands and Islamic principles. However, there are still questions regarding the real impact of this implementation on company value. This study aims to investigate the impact of implementing sharia accounting on firm value, taking into account the current developments in sharia accounting. Through this research, it is expected to provide a better understanding of how the application of Islamic accounting can affect company value and how the current development of Islamic accounting plays a role in this. The research method used is qualitative research using Literature Review or literature review. This study will discuss the impact of the application of Islamic accounting on firm value in the context of the current development of Islamic accounting, by considering aspects such as adherence to Islamic principles, access to Islamic markets, transparent disclosure of information, and the development of Islamic accounting standards. The results of this study are expected to provide better insight into the relationship between the application of Islamic accounting and firm value in the current context.Keywords: Sharia Accounting, Company, Sharia Accounting Standards.